2018
DOI: 10.1080/19336918.2018.1540903
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils as a source of branched-chain, aromatic and positively charged free amino acids

Abstract: Neutrophils release branched-chain (valine, isoleucine, leucine), aromatic (tyrosine, phenylalanine) and positively charged free amino acids (arginine, ornithine, lysine, hydroxylysine, histidine) when adhere and spread onto fibronectin. In the presence of agents that impair cell spreading or adhesion (cytochalasin D, fMLP, nonadhesive substrate), neutrophils release the same amino acids, except for a sharp decrease in hydroxylysine and an increase in phenylalanine, indicating their special connection with cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…It is now well-accepted that antimicrobial peptides influence the regulation of inflammation by directly affecting immune cells and inducing the synthesis of immune response mediators [ 14 ]. Neutrophil cells are a rich source of cationic antimicrobial peptides [ 45 , 46 ] and positively charged free amino acids [ 47 ]. Synthetic cationic peptides modulate the uptake of CpG-ODNs, which enhances the immunostimulatory effects [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is now well-accepted that antimicrobial peptides influence the regulation of inflammation by directly affecting immune cells and inducing the synthesis of immune response mediators [ 14 ]. Neutrophil cells are a rich source of cationic antimicrobial peptides [ 45 , 46 ] and positively charged free amino acids [ 47 ]. Synthetic cationic peptides modulate the uptake of CpG-ODNs, which enhances the immunostimulatory effects [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, tRNA transcription was low in the primary host cells (human granulocytes), but high in the cell lines, consistent with the observation that in humans, relatively few granulocytes are infected that support limited Ap growth and replication. Differentiated neutrophil granulocytes secrete branched-chain, aromatic and positively charged free amino acids upon adhesion to extracellular matrix (48), and inhibition of this response may increase availability to intracellular Ap (49). Evidence derived from in vitro studies of Ap and also in vivo with the related Anaplasma marginale indicates that microvascular endothelial cells are a nidus of infection (50)(51)(52), and these long-lived cells likely offer an environment supportive of growth and replication that requires import of amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of this study is the lack of control of the subjects' diet and the evaluation of gut microbiota, and there is the ambiguity that the walking protocols in this study have affected the gut microbiota composition. Furthermore, neutrophils are also one of the secretive sources of arginine, ornithine, lysine, hydroxylysine, histidine (38). Galkina et al (38) found that insulin significantly stimulated the amount of secreted hydroxylysine, a metabolite of lysine, in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, neutrophils are also one of the secretive sources of arginine, ornithine, lysine, hydroxylysine, histidine (38). Galkina et al (38) found that insulin significantly stimulated the amount of secreted hydroxylysine, a metabolite of lysine, in neutrophils. In addition, it has been reported that plasma concentrations of lysine positively associated with gestational diabetes mellitus through modifying IR and secretion (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation